2017
DOI: 10.18203/2394-6040.ijcmph20173325
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices about diabetes mellitus and its complications in T2DM patients attending the UHC in Mumbai

Abstract: Background: Diabetes Mellitus has become a major public health problem in India and also the major cause of disability through complications such as blindness, renal failure, lower limb gangrene etc. People suffering from Diabetes related complications are many times unaware about the measures to curb the onset of the complications. The aim of the study was to assess knowledge, attitude and practices about diabetes and its complications in the diabetic patientsMethods: This was a cross sectional descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This study was carried out among 125 type 2 diabetes attending RUHDC and more than half of the patients in this study had poor hypoglycemia symptoms knowledge and these findings was less than reported by Almalki et al [17] who reported 85% of patients had sufficient knowledge about the symptoms of hyperglycemia and this high percent is attributed to the fact that more than half of his patients received information about diabetes management from medical providers. On the other hand, Kazi and his colleagues [18] reported only 17.2%, whilst El-Khawaga from Egypt reported 48.1% [19].…”
Section: Discussionmentioning
confidence: 99%
“…This study was carried out among 125 type 2 diabetes attending RUHDC and more than half of the patients in this study had poor hypoglycemia symptoms knowledge and these findings was less than reported by Almalki et al [17] who reported 85% of patients had sufficient knowledge about the symptoms of hyperglycemia and this high percent is attributed to the fact that more than half of his patients received information about diabetes management from medical providers. On the other hand, Kazi and his colleagues [18] reported only 17.2%, whilst El-Khawaga from Egypt reported 48.1% [19].…”
Section: Discussionmentioning
confidence: 99%
“…11 • Some identified personal and social enablers in school going children are. 27,28 -Personal enablers: All participants reported perceived health benefits of physical activity. Fitness followed by Competence were the two important reasons why boys and girls participated in physical activity -Social enablers: Several participants mentioned active parents and sports role models as motivators for participating in physical activity.…”
Section: Risk Factors Facilitator Barriermentioning
confidence: 99%
“…11 • Some identified personal and social barriers in school going children are. 27,28 -Personal barriers: Private school girls cited body image related negative consequences of participating in a physical activity -Social barriers: Girls from both private and government schools faced more social censure for participating in physical activity. -Environmental barriers: Reduced opportunity for physical activity in schools was commonly reported across all participants.…”
Section: Risk Factors Facilitator Barriermentioning
confidence: 99%
“…Diabetes mellitus (DM) is a significant clinical and public health issue that only worsens. The World Health Organization (WHO) predicted that 190 million people across the world had diabetes in 2007, and that number is expected to rise to approximately 330 million by 2025 [1]. Nearly 80 percent of all non-traumatic lower limb amputations are caused by complications.…”
Section: Introductionmentioning
confidence: 99%